Development of Flight Simulator Control Trainer (FSCT) for Aviation Education - Othman, M. Aswad; Mohd. Hanif, Muhammad Syafiq; Khairul Amilin, Nur Aimi Nazihah; Anak Saing, Maureen Lizphine (Multidisciplinary Applied Research and Innovation, 2021)
The Flight Simulator Control Trainer was designed for learning purposes as we cannot get near the live aircraft. There are computer input devices designed to simulate the yoke, intended for flight simulator. As we know, a flight simulator is a machine designed to resemble an aircraft’s cockpit, with computer-generated images that mimic the pilot’s view and the aircraft’s motion. It is to relate with the yoke to help students to understand about the basic theory of flight because when using the digital way, it will help to attract students attention to use their knowledge on how the system work. Besides, students have no access to live aircraft, this is due to the fact that the live aircraft is very sensitive. Thus, we would like to take over the control surface part by using the control panel. So, the simulation method is preferable for training purposes. This Flight Simulator Control Trainer is to demonstrate the flight control system that bases on the module in Politeknik Banting Selangor which is DWM10082 Basic Aerodynamic.